TASK APPROACH AND PRINCIPLE PRINCIPLE PROSPECTS IN THE PEDAGOGICAL PROCESS - BASIS OF ACTIVATION OF PROFESSIONAL POSITION STUDENTS - Shcherbyna, S.M. (Pedagogy of Higher and Secondary Education, 2000)
This article is devoted to forming of active professional position of future teachers by means of using role perspective principle and problem approach during pedagogical training.